Improving the Quality of Meteorological Data and Services by Designing the Management Model of Information Systems and Information Technology - Seyyed Mohammad Aarabi; Tahmours Hasangholi Pourya Souri; AboAli Vedadhir; Pouria Pour Gharaei (Nīvār)
Production and use of complete and reliable data is the first step in providing optimal services and reliable weather and climatology studies. Incomplete data makes meteorological services and researches face a challenge. There are many ways to improve and restore data that one of the most important of which is the correct process management of collecting, transferring, storing and using data. The most important field that deals with this issue is the management information systems and information technology. The way of managing this area and coordinating it with the main strategies and other sectors plays a significant role in reducing the data gaps and insufficient data and also improving the quality and quantity of meteorological and climatological data and information, and improving the services of the organization. In this regard, it is considered to identify the strategies of information systems and information technology and its main subsystems to create more coordination between the various components of the organization and finally to produce and use valid and sufficient data. In this article, in order to optimally manage the production and analysis of meteorological data, the design and exploration of the model was discussed with the in-depth and semi-structured interview method. This process was carried out with the participation of 20 data and information experts of the country's meteorological organization, who were selected purposefully and with the help of the content analysis method, with the aim of achieving various aspects of information systems and information technology function. Then the basic concepts and also the reliability of this method were studied. The method of data analysis (Manual and software with MAXQDA10) is a combined content analysis with an inductive and deductive approach, and the acceptability and objectivity of the data is done by combining data collection, multi-dimensional, diversity of research participants, frequent review and revision of data. The final findings of the research with 61indicators, 20categories and 5 themes include "information systems & information technology", "meteorological information infrastructure and technology", "meteorological data and information management", "meteorological service management" and "meteorological information and communication security" and in each of them four subclasses with the help of strategic reference points method was determined. In the end, with the re-review and opinion of respected professors of the university, the relationships of the main themes in the form of information systems and meteorological information technology with the four subsystems and the strategies of each one were drawn in order to create more coordination in decision-making to improve data management and meteorological services